Impact of differential group delay and environmental factors on signal quality in multimode fiber using NRZ and QAM modulation - Oyibo Dafe Precious; Samuel Oghenemega Shaka; Enoh Pius Ogherohwo; Cletus Olisenekwu; Agbosa Tobore Roseline; Godwin Kparobo Agbajor (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2025)
This study investigates the effects of polarization mode dispersion (PMD) on high-speed multimode fiber (MMF) optical communication systems, focusing on how differential group delay (DGD) and environmental conditions such as temperature and humidity influence signal quality. The research was conducted in Abuja, Nigeria, using two modulation formats—non-return-to-zero (NRZ) and quadrature amplitude modulation (QAM). Experimental measurements were carried out over fiber lengths ranging from 1 km to 38 km, and data rates from 15 Gbps to 240 Gbps. Key performance metrics such as bit error rate (BER), jitter, and signal-to-noise ratio (SNR) were analyzed in relation to DGD under varying environmental conditions. Results showed that DGD increased from 0.136 ps to 2.78 ps for NRZ and from 0.058 ps to 2.24 ps for QAM across the tested fiber lengths. Corresponding BER values for NRZ ranged from 1.18 × 10-7 to 1.35 × 10-7, while QAM showed slightly better performance with BER values between 1.18 × 10-7 and 1.29 × 10-7. Jitter rose from 4.26 ps to 31.20 ps in NRZ and from 4 ps to 33.54 ps in QAM. SNR values declined as DGD increased, with NRZ dropping from 34.59 dB to 54.56 dB and QAM from 34.83 dB to 52.90 dB. Environmental factors also played a role; temperature increases from 28.34°C to 29.90°C and humidity from 53.1% to 59.5% led to significant increases in DGD. The findings confirm that PMD, though less dominant in MMF than modal dispersion, still significantly affects signal quality in long-distance and high-speed MMF systems. QAM demonstrated greater resilience to PMD compared to NRZ. This study highlights the need for effective dispersion management and modulation format optimization in designing robust optical networks for environmentally dynamic regions like Abuja.